SPEECH COMPREHENSION IMPAIRMENT IN SCHIZOPHRENIA - Kadek Ari Sintya Dewi; Ida Bagus Putra Yadnya; I Wayan Mulyawan (ULIL ALBAB : Jurnal Ilmiah Multidisiplin, 2022)
Abstract: The objective of this study was to look into the speech comprehension impairment of the schizophrenic main character in the Words on Bathroom Walls movie. A descriptive qualitative method was used in this study. It is concerned with the description of data in the form of the schizophrenic's utterances. The findings of the study demonstrate that only six of the eight types of schizophrenic speech comprehension impairments exist. The types of speech comprehension impairments noticed in Adam were weakening of goal, poverty of speech, looseness, peculiar logic, distractibility, and perseveration. The TLI (Thought and Language Index) theory by Liddle (2002) was used to make this classification.